High Risk First Degree Relatives of Type 1 Diabetics: An Association with Increases in CXCR3+ T Memory Cells Reflecting an Enhanced Activity of Th1 Autoimmune Response - Tanja Milicic; Aleksandra Jotic; Ivanka Markovic; Katarina Lalic; Veljko Jeremic; Ljiljana Lukic; Natasa Rajkovic; Dušan Popadic; Marija Macesic; Jelena P. Seferovic; Sandra Aleksic; Jelena Stanarcic; et al. (International Journal of Endocrinology)
We analyzed the level of (a) CXCR3+ (Th1) and CCR4+ (Th2) T memory cells (b) interferon-γ inducible chemokine (IP-10)(Th1) and thymus and activation-regulated chemokine (TARC)(Th2), in 51 first degree relatives (FDRs) of type 1 diabetics (T1D) (17 high risk FDRs (GADA+, IA-2+) and 34 low risk FDRs (GADA−, IA-2−)), 24 recent-onset T1D (R-T1D), and 18 healthy subjects. T memory subsets were analyzed by using four-color immunofluorescence staining and flowcytometry. IP-10 and TARC were determined by ELISA. High risk FDRs showed higher levels of CXCR3+ and lower level of CCR4+ T memory cells compared to low risk FDRs (64.98 ± 5.19 versus 42.13 ± 11.11; 29.46 ± 2.83 versus 41.90 ± 8.58%, resp., P<0.001). Simultaneously, both IP-10 and TARC levels were increased in high risk versus low risk FDRs (160.12 ± 73.40 versus 105.39 ± 71.30; 438.83 ± 120.62 versus 312.04 ± 151.14 pg/mL, P<0.05). Binary logistic regression analysis identified the level of CXCR3+ T memory cells as predictors for high risk FDRs, together with high levels of IP-10. The results imply that, in FDRs, the risk for T1D might be strongly influenced by enhanced activity of Th1 and diminished activity of Th2 autoimmune response.